Resistance spot welding of stainless steel and mild steel - Wan Muhammad Hafizi, Wan Hassan (2012)
Resistance spot welding (RSW) is commonly used in manufacturing and automotive industry; because of their advantages such as high speed and high production, suitability for automation, easily to process and low cost. This project deals with the investigation of microstructure and mechanical properties of weld joint of Stainless Steel and Mild Steel. The main objective of this project is to investigate the weldability of stainless steel and steel weld. For design of experiment, Taguchi method was employed by using Minitab software, and total nine (9) sets experiment was conducted. The studies of mechanical properties, are consists by using three (3) tests; Tensile test, Charpy test, and microstructure to analyze and investigate the weldability of Stainless Steel and Mild Steel sheet. As a result, higher Tensile strength and Charpy toughness is due to increase in width and depth of weld nugget. Optimum specimen has higher width and depth than experimental specimen. Based on Taguchi analysis, the best combination of parameters is Current (5.0 kA), Weld Time (3.0 cycle) and Pressure (40 psi). The rank of parameter affected the resistance spot welding experiment is Current, Pressure and Weld Time respectively. Based on Regression analysis, the equation of Tensile strength and Charpy toughness were generated. As for recommendation, the other parameters such as diameters of electrode and hold time can be added in experiment. For conclusion, Taguchi analysis is verified with verification experiment.